Representações do diabo na literatura e no cinema: o caso da adaptação fílmica de O Exorcista e sua recepção no Brasil - Viana, João Vitor Temóteo (2023)
The act of storytelling has accompanied humanity since the dawn of its existence. In this sense, certain stories are perpetuated in the popular imagination and passed on between different generations and cultures, causing them to undergo certain modifications. When analyzing the Western cultural context, one of the most prominent characters in these narratives, which are continually altered and passed on, is the Devil, a multifaceted entity portrayed from different perspectives and with different objectives. In view of this scenario, this research seeks to analyze under what circumstances the process of adapting the diabolical being from the novel The Exorcist (1971), by William Peter Blatty (1928-2017), to the homonymous film directed by William Friedkin (1935-2023) and released in 1973, took place. Based on the work of Linda Hutcheon (1947-) and Patrick Cattrysse (1957-), the adaptive phenomenon is understood here as a form of translation, that is, a creative transcoding of one system of signs into another. In addition to studying how the figure of the Devil was translated, this work seeks to investigate the reception of the feature film by the Brazilian public at the time of its arrival, by observing what was reported by four press outlets with wide circulation at the time. The ideas of Marcos Almeida (2010) and Luigi Schiavo (2000) will be used as a basis for thinking about the Devil. The results obtained point to the fact that, although the book and film converge in a diabolical representation that establishes strong dialogues with the versions of the Devil contained in the Bible and in more traditional perspectives on this character, it can be seen that the film opts for a greater focus on the entity's bodily and physical component, while the written text moves towards a theological and philosophical reflection on Evil. As for the Brazilian public's reaction to the adaptation, even with the high expectations created, the full-length film did not have an impact like that seen in other countries, mainly because of the differentiated relationship that part of Brazilian society has with the diabolical figure.